2014
DOI: 10.1161/circresaha.115.304353
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of Bone Marrow From Patients With Ischemic Heart Disease and Left Ventricular Dysfunction

Abstract: Rationale Bone marrow (BM) cell therapy for ischemic heart disease (IHD) has shown mixed results. Before the full potency of BM cell therapy can be realized, it is essential to understand the BM niche following acute myocardial infarction (AMI). Objective To study the BM composition in patients with IHD and severe left ventricular dysfunction (LVD). Methods & Results BM from 280 patients with IHD and LVD were analyzed for cell subsets by flow cytometry and colony assays. BM CD34+ cell percentage was decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…It is noteworthy that Circulation Research has recently published another report from the Cardiovascular Cell Therapy Research Network (CCTRN) comparing composition and functionality of BMC collected from patients with ST-segment-elevation myocardial infarction at different times after MI (in TIME and LateTIME trials) and from patients with chronic ischemic heart failure (in the Effectiveness of Stem Cell Treatment for Adults With Ischemic Cardiomyopathy, the FOCUS Study). 22 Interestingly, in that study, the same authors of the present work showed a positive correlation of BM CD34 + precursors and a negative correlation of CD11b + cells with recovery of cardiac function as assessed by left ventricular ejection fraction. The discrepancy between those findings and data presented in this issue can be attributed, at least in part, to the distinct end point chosen and to the extended cohort used to generate the former.…”
Section: Article See P 99supporting
confidence: 60%
“…It is noteworthy that Circulation Research has recently published another report from the Cardiovascular Cell Therapy Research Network (CCTRN) comparing composition and functionality of BMC collected from patients with ST-segment-elevation myocardial infarction at different times after MI (in TIME and LateTIME trials) and from patients with chronic ischemic heart failure (in the Effectiveness of Stem Cell Treatment for Adults With Ischemic Cardiomyopathy, the FOCUS Study). 22 Interestingly, in that study, the same authors of the present work showed a positive correlation of BM CD34 + precursors and a negative correlation of CD11b + cells with recovery of cardiac function as assessed by left ventricular ejection fraction. The discrepancy between those findings and data presented in this issue can be attributed, at least in part, to the distinct end point chosen and to the extended cohort used to generate the former.…”
Section: Article See P 99supporting
confidence: 60%
“…2 There is a growing interest in the BM status in patients with cardiovascular disease or risk factors. 11,12 For instance, acute myocardial infarction induces BM metabolic activation, 13 and failure of the BM to mobilize CD34 + cells post-acute myocardial infarction is associated with a poor outcome. 14 In diabetes mellitus, especially with vascular disease, the BM undergoes extensive remodeling and stem cell mobilization is impaired.…”
Section: Cd34 + Cells Predict Mortality 233mentioning
confidence: 99%
“…9 A series of larger trials performed under the auspices of the CCTRN had suggested the absence of therapeutic benefit of bone marrow-derived mononuclear cells after myocardial infarction. 10 Human bone marrow is a desirable source because of accessibility for harvest, favorable biological profile, and extensive clinical experience.…”
Section: Article See P 867mentioning
confidence: 99%
“…13 In consideration of more favorable outcomes reported in European trials predating the CCTRN effort, 14,15 the present analysis was undertaken to evaluate whether the material content of bone marrow mononuclear cells may underpin disparate results. 9 To this end, flow-cytometry and colony assays mined for regenerative propensity within heterogeneous mixtures of bone marrow cellular compartments. Bone marrows exhibiting increased CD34 + and decreased CD11b + cell content were found to confer an ejection fraction benefit both in the setting of acute and chronic left ventricular dysfunction.…”
Section: Article See P 867mentioning
confidence: 99%
See 1 more Smart Citation